An application of the context transfer protocol: IPsec in a IPv6 mobility environment. (19th February 2008) - Allard, Fabien; Bonnin, Jean-Marie
The use of the internet must be able to be in confidence for users but security provisioning has a cost for Internet Service Providers (ISPs). In a mobility context, this security must be set up from scratch after each handover and for each customer. Therefore, a mechanism has been designed in standardisation bodies: the Context Transfer. This mechanism aims to transfer suitable information between equipments in order to reduce handover time. The benefit for an operator would then be a same security level during and after handover in mobile networks but with a cost as lower as possible. After a state of the art of context transfer for security, this paper quickly presents the Context Transfer Protocol (CXTP) defined at the Internet Engineering Task Force (IETF). Then, it defines the IPsec context and finally, it describes a CXTP-based solution to transfer this context between two access routers in a IPv6 mobility environment.